Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Intrinsik Dan Motivasi Ekstrinsik Terhadap Kinerja Karyawan Pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Tanah Laut - Ahmad Dedi Fernadi; Dwi Wahyu Artiningsih; Noor Hidayati (JURNAL BISNIS DAN PEMBANGUNAN, 2016)
The purpose of this study: (1) Know and analyze the influence of Transformational Leadership Style on Employee Performance, (2) Determine and analyze the influence of Intrinsic Motivation on Employee Performance, and (3) Know and analyze the influence of the Employee Performance Extrinsic Motivation.The population in this study were all employees of the Regional Water Company (PDAM), Tanah Laut District totaling 48 people. The technique used is the technique of sampling saturated with the overall number of population sampled. Collecting data using questionnaires designed using level Likert scale 1-5. Analysis of the data using structural models SmartPLS.The results showed: (1) Transformational Leadership Style significant effect on the performance of employees amounted to 31.25%, based on the significant influence of Transformational Leadership Style it is expected that the leadership of the company to maintain the values contained in Transformational Leadership Style thereby giving encouragement to employees to increase their performance , (2) intrinsic Motivation significant effect on the performance of employees amounted to 35.32%, based on intrinsic Motivation is expected to significantly influence the management / leadership of the company increases intrinsic motivation given to encourage employees to increase their performance, and (3) Extrinsic motivation significantly influence employee performance amounted to 35.63%, based on the expected significant influence extrinsic motivation management / leadership of the company increased extrinsic motivation given to encourage employees to increase their performance. Keywords : Transformational Leadership, Intrinsic Motivation, Extrinsic Motivation and Employee Performance.